Electrical and spectroelectrochemical investigation of thiophene-based donor-acceptor copolymers with 3,4-ethylenedioxythiophene - Araujo,Marcus Henrique de (2020)
Abstract This work reports the spectroelectrochemical and electrical behavior of electropolymerized donor-acceptor like (D-A) copolymer films, based on 3,4-ethylenedioxythiophene (EDOT) and beta-substituted electron-acceptor thiophenes. Initially, the copolymer films were deposited on indium tin oxide substrates, which spectroelectrochemistry measurements were carried out with an UV-Vis spectrophotometer. Hence, it was possible to observe the electrochromic properties of these materials, visualizing the color changing towards different potentials applied. The experiments have shown that these D-A like copolymers presented good electrochromic properties, such as optical contrast, coloration efficiency, and switching times. Additionally, films prepared on a platinum working electrode were investigated by electrochemical impedance spectroscopy, which has shown the electrical behavior of those copolymers and their potential as candidates to capacitive devices building. Therefore, the combination of electron-donor EDOT with those electron-acceptor monomers is indeed a useful strategy to tailoring and fine-tuning the physicochemical properties of polythiophenes with innovative applications.